Complete atrioventricular block in acute coronary syndrome: prevalence, characterisation and implication on outcome. Issue 3 (April 2018) - Aguiar Rosa, Silvia; Timóteo, Ana Teresa; Ferreira, Lurdes; Carvalho, Ramiro; Oliveira, Mario; Cunha, Pedro; Viveiros Monteiro, André; Portugal, Guilherme; Almeida Morais, Luis; Daniel, Pedro; Cruz Ferreira, Rui
Purpose: The aim was to characterise acute coronary syndrome patients with complete atrioventricular block and to assess the effect on outcome. Methods: Patients admitted with acute coronary syndrome were divided according to the presence of complete atrioventricular block: group 1, with complete atrioventricular block; group 2, without complete atrioventricular block. Clinical, electrocardiographic and echocardiographic characteristics and prognosis during one year follow-up were compared between the groups. Results: Among 4799 acute coronary syndrome patients admitted during the study period, 91 (1.9%) presented with complete atrioventricular block. At presentation, group 1 patients presented with lower systolic blood pressure, higher Killip class and incidence of syncope. In group 1, 86.8% presented with ST-segment elevation myocardial infarction (STEMI), and inferior STEMI was verified in 79.1% of patients in group 1 compared with 21.9% in group 2 ( P <0.001). Right ventricular myocardial infarction was more frequent in group 1 (3.3% vs. 0.2%; P <0.001). Among patients who underwent fibrinolysis complete atrioventricular block was observed in 7.3% in contrast to 2.5% in patients submitted to primary percutaneous coronary intervention ( P <0.001). During hospitalisation group 1 had worse outcomes, with a higher incidence of cardiogenic shock (33.0% vs. 4.5%; P <0.001), ventricular arrhythmias (17.6% vs. 3.6%; P <0.001) and the need for invasive mechanical ventilation (25.3% vs. 5.1%; P <0.001). After a propensity score analysis, in a multivariate regression model, complete atrioventricular block was an independent predictor of hospital mortality (odds ratio 3.671; P =0.045). There was no significant difference in mortality at one-year follow-up between the study groups. Conclusion: Complete atrioventricular block conferred a worse outcome during hospitalisation, including a higher incidence of cardiogenic shock, ventricular arrhythmias and death.